Increased antibody titers but induced T cell AICD and apoptosis response in COVID-19 convalescents by inactivated vaccine booster - Jingmin Zhao; Han Zhang; Lina Jiang; Fang Cheng; Wei Li; Zihao Wang; Hongyang Liu; Shaohua Li; Yiyun Jiang; Meiling Li; Yan Li; Shuhong Liu; et al. (Microbiology Spectrum, 2024)
ABSTRACTIt is urgently needed to evaluate the necessity and benefits of booster vaccination against the coronavirus 2 of the severe acute respiratory syndrome (SARS-CoV-2) Omicron to facilitate clinical decision-making for 2019 coronavirus disease (COVID-19) convalescents. We conducted a multicenter, prospective clinical trial (registration number: ChiCTR2100045810) in the first patients with COVID-19 from 28 January 2020 to 20 February 2020 to assess the long-term durability of neutralizing antibodies against live Omicron BA.5 and further assess the efficiency and safety of CoronaVac in the convalescent group. A total of 96 COVID-19 convalescents were enrolled in this study. Neutralizing antibody titers in convalescents were significantly reduced in 9–10 months. A dose-refreshing vaccination in 28 convalescents with an antibody titer below 96 significantly induced neutralizing antibodies against live Omicron by 4.84-fold. Meanwhile, the abundance of naive T cells increased dramatically, and TEMRA and TEM cells gradually decreased after vaccination. Activation-induced cell death and apoptosis-related genes were significantly elevated after vaccination in all T-cell subtypes. One-dose booster vaccination was effective in inducing a robust antibody response against SARS-CoV-2 Omicron in COVID-19 convalescents with low antibody titers. However, vaccine-mediated T-cell consumption and regeneration patterns may be detrimental to the antiviral response.IMPORTANCEThe globally dominant coronavirus 2 of the severe acute respiratory syndrome (SARS-CoV-2) Omicron variant raises the possibility of repeat infections among 2019 coronavirus disease (COVID-19) convalescents with low neutralizing antibody titers. The importance of this multicenter study lies in its evaluation of the long-term durability of neutralizing antibodies in COVID-19 convalescents and the efficacy of a booster vaccination against the live Omicron. The findings suggest that a one-dose booster vaccination is effective in inducing a robust antibody response against SARS-CoV-2 Omicron in convalescents with low antibody titers. However, the study also highlights the potential detrimental effects on the antiviral response due to vaccine-mediated T-cell consumption and regeneration patterns. These results are crucial for facilitating clinical decision-making for COVID-19 convalescents and informing public health policies regarding booster vaccinations.